Choclo virus (CHOV) recovered from deep metatranscriptomics of archived frozen tissues in natural history biorepositories. - Paris S Salazar-Hamm; William L Johnson; Robert A Nofchissey; Jacqueline R Salazar; Publio Gonzalez; Samuel M Goodfellow; Jonathan L Dunnum; Steven B Bradfute; Blas Armién; Joseph A Cook; Daryl B Domman; Darrell L Dinwiddie (Public Library of Science (PLoS), 2024)
Background Hantaviruses are negative-stranded RNA viruses that can sometimes cause severe disease in humans; however, they are maintained in mammalian host populations without causing harm. In Panama, sigmodontine rodents serve as hosts to transmissible hantaviruses. Due to natural and anthropogenic forces, these rodent populations are having increased contact with humans. Methods We extracted RNA and performed Illumina deep metatranscriptomic sequencing on Orthohantavirus seropositive museum tissues from rodents. We acquired sequence reads mapping to Choclo virus (CHOV, Orthohantavirus chocloense) from heart and kidney tissue of a two-decade old frozen museum sample from a Costa Rican pygmy rice rat (Oligoryzomys costaricensis) collected in Panama. Reads mapped to the CHOV reference were assembled and then validated by visualization of the mapped reads against the assembly. Results We recovered a 91% complete consensus sequence from a reference-guided assembly to CHOV with an average of 16X coverage. The S and M segments used in our phylogenetic analyses were nearly complete (98% and 99%, respectively). There were 1,199 ambiguous base calls of which 93% were present in the L segment. Our assembled genome varied 1.1% from the CHOV reference sequence resulting in eight nonsynonymous mutations. Further analysis of all publicly available partial S segment sequences support a clear relationship between CHOV clinical cases and O. costaricensis acquired strains. Conclusions Viruses occurring at extremely low abundances can be recovered from deep metatranscriptomics of archival tissues housed in research natural history museum biorepositories. Our efforts resulted in the second CHOV genome publicly available. This genomic data is important for future surveillance and diagnostic tools as well as understanding the evolution and pathogenicity of CHOV.